Emotion recognition : a pattern analysis approach - Konar, Amit.; Chakraborty, Aruna, 1977- (2014)
"Written by leaders in the field, this book provides a thorough and insightful presentation of the research methodology on emotion recognition in a highly comprehensive writing style. Topics covered include emotional feature extraction, facial recognition, human-computer interface design, neuro-fuzzy techniques, support vector machine (SVM), reinforcement learning, principal component analysis, the hidden Markov model, and probabilistic models. The result is a innovative edited volume on this timely topic for computer science and electrical engineering students and professionals"--
Includes index.
Keywords: Human-computer interaction; Artificial intelligence; Emotions -- Computer simulation; Pattern recognition systems; Context-aware computing; TECHNOLOGY & ENGINEERING / Electronics / Digital; COMPUTERS / Computer Vision & Pattern Recognition